Severity of Stress in Acne Patients Attending Dermatology Outpatient Department of Tertiary Hospital in Kathmandu - Amrita Shrestha; Dinesh Binod Pokhrel; Sudip Parajuli; Manisha Chapagain; Rabina Shrestha (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Stress persists when a person is unable to cope with the situations of the past, present or future. Stress may be associated with physical and psychological abnormalities. Acne vulgaris is a chronic inflammatory disease of the pilo-sebaceous units with prevalence of more than 85% in adolescent age group.